Relationships Between Phonological Awareness and Reading in Spanish: A Meta‐Analysis. Issue 1 (26th October 2021) - Míguez‐Álvarez, Carla; Cuevas‐Alonso, Miguel; Saavedra, Ángeles
Abstract: Previous meta‐analyses of the relationship between phonological awareness (PA) and reading have been conducted mostly in children who speak English, a language with an opaque writing system. In this study, we present a meta‐analysis that examined mean correlations between three PA tasks testing phonemic, syllabic, and intrasyllabic awareness and three reading tasks testing word reading, nonword reading, and reading comprehension in Spanish, a language with a near‐transparent writing system. A random‐effects model of 47 articles ( N = 7, 956) was used for a multiple correlation study that showed a significantly moderate correlation between some of the PA subcategories and the reading tasks in Spanish‐speaking children. The largest correlation values were found between syllabic awareness and reading, which highlights the importance of syllable recognition during reading acquisition. In addition, we found that intrasyllabic awareness also plays an important role in reading in Spanish. The findings are discussed from a cross‐linguistic perspective. Abstract :